[The Impact of Alternative Government Policies Under Varying Exchange Systems]: Reply - Krueger, Anne O. (Quarterly Journal of Economics, 1968)
Journal Article The Impact of Alternative Government Policies under Varying Exchange Systems: Reply Get access Anne O. Krueger Anne O. Krueger University of Minnesota Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 82, Issue 3, August 1968, Pages 511–513, https://doi.org/10.2307/1879523 Published: 01 August 1968